Memahami Dasar Filosofis Hukum Ekonomi Islam - Miftahul Ulum (Institut Ilmu Keislaman Annuqayah, 2017)
The purpose of this paper is to explain the urgency of understanding the basic philosophical economy of Islamic banking in the dynamics of global economic competition. The basic principle of Islamic economic law is different from the conventional economic system which is not based on the teachings of religion as the main basis in every application of economic transactions. In Islamic economic law it is always emphasized the basic principle that becomes universal value for the achievement of society prosperity, that is, faith, justice, equilibrium, and equity for all parties. All the basic objectives and principles implemented in the Islamic economy are inseparable from God's law, while conventional economics is based on the results of human thought and ideology. The results of this study indicate that the basic principle of Islamic economic law is to avoid thep prohibited things in the teachings of religion, such as usury or other transactions that are more concerned with profit than the values of justice for the benefit of the ummah or society in general. This is because the basic principles of Islamic economic law is always guided by the Islamic teaching source, namely al-Quran, sunnah, ijma, and qiyas